Design as an Isolating Mechanism for Capturing Value from Innovation: From Cloaks and Traps to Sabotage - Sharapov, Dmitry; MacAulay, Samuel C. (Academy of Management Review, 2022)
How firms capture value from their innovations has long interested strategy and innovation scholars. Prior work has focused on legal, economic, and social mechanisms for isolating knowledge from imitation as crucial to this process. Our contribution extends this stream of research by identifying how design choices about the way knowledge is manifested (e.g., into routines, blueprints, prototypes, or products) can inhibit a counterparty’s ability to imitate knowledge relating to a focal innovation. We derive six theoretically distinct types of knowledge manifestation that can be used for these ends, consider their impacts on the awareness, motivation, and capability of a counterparty seeking to imitate the focal knowledge, and organize them into a novel two-dimensional conceptual framework for comparison. By doing so, we add design mechanisms to the strategic toolbox of isolating mechanisms available for capturing value from innovation. This addition opens up a new channel through which organizational choice endogenously shapes appropriability regimes and introduces knowledge manifestations as an important unit of analysis for understanding innovation strategy.